Exploring the legal aspects and court process of forensic entomology from the Malaysia’s perspective - Suzana Muhamad Said,; Raja Muhammad Zuha Raja Kamal Bashah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
This paper seeks to explore the legal aspects and court process relating to forensic entomology with reference to Malaysia. It aims to inform the non-legal person of the court process and giving of evidence in Malaysia’s court by expert witnesses such as forensic entomologist. The methodology used is a socio-legal analysis with reference to legal texts and statutes in Malaysia. Online search on the number of reported cases published in two legal journals relating to evidence by forensic entomologist was conducted. The finding from the reported cases where entomologist testify in court as an expert witness is scarce and so few assumptions were made on this. A brief case studies on the selected reported cases were chosen to explain the use of forensic entomology in the court process. This paper suggests that entomologists’ evidence on the issue of the time of death is important as accordingly, a charge sheet in the homicide cases must contain the time of death and prove in court. It is also suggested that recognition is given to forensic entomologists and that the Allied Health Professions Act 2016 [Act 774] which to regulate the practise of allied health of professionals including entomologists, be in force soon.